A Review Clinical Decision Support System using Ontology - Rawia Mohamed-Najeeb Abu Amr, Lailatul Qadri Zakaria, Waidah Ismail (International Journal of Advanced Science and Technology, 2020)
A decision support system (DSS) is an intelligent system by which a decision support is provided for decision-making purpose. DSS extensively requires a representation of domain knowledge to apply reasoning methods that help in reaching new knowledge for decision support. Due to the benefits of Ontology compared with database system, it considered as knowledge representation in several DSS. DSSs have been extensively addressed in many research like healthcare, therefore it was named Clinical Decision Support System (CDSS). In this paper, a review on reasoning methods that has been utilized on CDSS has been conducted. The review is achieved through comparing and analysing the benefits and drawbacks of CDSS reasoning methods as well as surveying the current reasoning methods used in ontology based CDSS. After analysis, it has been revealed that the integration of the Case-Based Reasoning (CBR) method and Rule-Based Reasoning (RBR) methods facilitates the operation of CDSS to mimic clinical staff members. This integration is recommended since the CDSS will contain the two sources of knowledge which are domain knowledge and knowledge from historical cases. Furthermore, the review shows that ontology has been used in several CDSS but still not been integrated with CBR and RBR.